PENERAPAN PENDEKATAN INQUIRI DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 014 BASILAM BARU - Darbi, Ahmad Darbi Ahmad; Alpusari, Mahmud Alpusari Mahmud; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The problem is research in this study is the result of third-grade students learn science SDN 014 Basilam Baru still low or insufficient KKM set by the school at 65, which reaches only 11 people KKM 47.28% for the classically expected learning research with the application of the inquiry approach to the formulation of the problem